Aplikasi Augmented Reality (AR) Sebagai Media Pembelajaran Sistem Rangka Manusia - Kaharuddin Kaharuddin; Yonky Pernando; Marfuah Marfuah; Musliadi KH (Journal of Information System Research (JOSH), 2023)
Problems in the Indonesian education system have raised serious concerns over the low quality of education. One of the problems that causes low interest in learning is the lack of interest in the learning media used. Therefore, it is important for schools to create learning conditions that are comfortable, interesting, and provide opportunities for students to participate actively. One solution that can be used is the use of computer-based learning media, such as Augmented Reality (AR), which can increase students' interest in learning. In the context of learning Natural Sciences, understanding the anatomy of the human body is an important aspect. The purpose of this research is to develop an Augmented Reality (AR) application using the Game Development Life Cycle (GDLC) method as a learning medium or introduction to the human skeletal system. This application will be equipped with theoretical materials and 3D-based object views that include the names of related bones. With the development of this application, it is expected to create an interesting and interactive learning experience, increase the effectiveness of the learning process, and avoid boredom for students.